A study on the perception of male librarians and library paraprofessionals of the University of the Philippines and Rizal Library of Ateneo de Manila University on librarianship as their profession in relation to their gender - Macalanda, Angelie Mae D. (2007)
Librarianship as a profession derives its specific tasks and responsibilities from standards such as Republic Act 9246 or the Philippine Librarianship act, the Librarians' Code of Ethics and is regulated through the Licensure Examination. In this regard, written codes describe their roles; on the other hand, their patrons, colleagues and the library environment from in the workplace prescribe patterns on how they do their work. Therefore, the definition of a librarian's role goes beyond what is written in the codes, and is contextualized in the library environment where he/she belongs. Employing a greater number of women than men, librarianship is labeled as a "feminized profession," wherein it is usually described to be related to nursing and childcare, wherein men are considered a minority and are argued to be endowed with specific roles apart from the librarian in general.